The role of church based organisations in peace building: case study of CCJP Masvingo Diocese 2008 -2013 - Manavele, Prosper (Midlands State University, 2014)
This study seeks to find out the role of church based organizations in peace building using the case study of CCJP Masvingo Diocese from 2008 to 2013.The study takes a look on the nature of political violence that occurred in Masvingo in 2008 which was characterized by the use of hate speech, beatings, torture, murder, destruction of houses and property. Violence hotspots are also highlighted in the study which includes Zaka, Bikita, Chiredzi and Nerupiri. The study goes on to look into the peace building initiatives introduced by CCJP after the 2008 violence which includes peace building training for peace committees, peace events, youth voices forums, community visioning workshops and outreach strategies for youth leaders workshops. The successes and challenges of peace building are highlighted and successes include increase in political tolerance, reduction in cases of political violence, collaboration from different political parties in community projects and active participation of women and the challenges include budgetary constraints, antagonism between the state and civil society and poor state of roads in rural areas. A conclusion was drawn and some recommendations were made out by the researcher basing on the research findings of the study.